Making sense of child, early and forced marriage among Syrian refugee girls: a mixed methods study in Lebanon. Issue 1 (7th January 2018) - Bartels, Susan Andrea; Michael, Saja; Roupetz, Sophie; Garbern, Stephanie; Kilzar, Lama; Bergquist, Harveen; Bakhache, Nour; Davison, Colleen; Bunting, Annie
Abstract : Introduction: The Syrian conflict has resulted in over 2.3 million child refugees in the Middle East and the prevalence of early marriage has reportedly increased among displaced Syrian families. This study explores the underlying factors contributing to child marriage among Syrian refugees in Lebanon with the goal of informing community-based strategies to address the issue. Methods: In July–August 2016, trained interviewers collected self-interpreted stories in Lebanon using Cognitive Edge's SenseMaker, a mixed-method data collection tool. Participants included married and unmarried Syrian girls, Syrian parents as well as married and unmarried men. Each participant shared a story about the experiences of Syrian girls and then interpreted the story by plotting their perspectives on a variety of questions. Patterns in the responses were analysed in SPSS and the accompanying qualitative narratives were reviewed to facilitate interpretation of the quantitative results. Results: 1422 self-interpreted stories from 1346 unique participants were collected with 40% of shared stories focused on (n=332) or mentioning (n=245) child marriage. Quantitative data summarised the different perspectives of female and male participants. Syrian girls and mothers were more likely to share stories about protection/security and/or education and were more likely to report that girls were overprotected. Male participants were more likely to share stories about financial security as well as sexual exploitation of girls and more often reported that girls were not protected enough. Despite these gendered perspectives, many of the shared narratives highlighted similar themes of financial hardship, lack of educational opportunities and safety concerns around sexual and gender-based violence (SGBV). Conclusions: A complex myriad of factors contribute to early marriage including poverty, lack of educational opportunities and concerns about SGBV. Sexual exploitation under the guise of marriage is a reality for some Syrian girls. Gender-specific strategies to address child marriage might be more effective in reducing this harmful practice.